Happiness, demographic variables, and self-perception as predictors of job satisfaction among factory employees in Malaysia - A Manaf, Aini Maznina; Tengku Azzman, Tengku Siti Aisha; Idid, Syed Arabi (Taylor’s University, 2021)
In general, job satisfaction is a primary concern of managers in organisations. The general belief that “a happy employee is a productive employee” often prompts managers to prioritise employee satisfaction at work. The importance of employee job satisfaction in the workplace has led to many studies in this area. Nevertheless, no conclusive findings have been established on the contributing factors that influence job satisfaction. The purpose of this study is to examine the relationship of factors such as happiness, self-perception, and demographics with job satisfaction. A survey was conducted involving 475 Malaysian factory employees in Selangor, Perak, Pahang, and Kedah. A series of ANOVA and zero-order correlations tests were carried out to answer the research questions and prove the hypotheses of the study. The findings reveal that happiness, income, and self perception demonstrate a significant relationship with job satisfaction. Employees who are happy and perceive others as happy tend to be satisfied with their job. Similarly, employees who have a good perception of their personal life, family, and country are satisfied with their job. Consistent with the majority of previous studies, employees who earn a high income tend to be more satisfied with their job. In contrast, the tenure and level of education do not demonstrate a significant relationship with job satisfaction. The duration of employment with an organisation and the certificates or degrees attained also do not predict job satisfaction. Using the framework of the Herzberg two-factor theory in a factory setting, this study expands this theory to organisational communication studies, particularly on job satisfaction. Practical implications of the study are also discussed in this paper.